The great masters of modern surgery (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The aim of my publication is to make a biographical sketch of the most influential and innovative surgeons in modern surgery, based on scientific positivism. The period on study is between 1.850 and 2.000
Keywords: Modern surgery. Leaders of 20th century surgery